The assessment of the usage, attitude, and image of Filipino students utilizing motorcycle taxi hailing services as alternative transportation in the NCR - Abadilla, John Carlo L., Biscocho, Joshua C., Manaoat, Rappunzel L., Manaois, Karl Nikolai O., Matienzo Jr., Rommel T. 4 0 16; 5
Abstract As various transportation modalities continue to rise, Motorcycle Taxi Hailing Services (MTHS) has reshaped traditional modes of transportation. The evolving landscape of MTHS has brought a significant shift in the transportation sector, particularly amid the country's extreme traffic congestion. This study employed the Usage, Attitude, and Image (UAl) Study by Ned Roberto (1996) with 401 valid respondents. The research examined demographic profiles, extent of usage, levels of attitude, and the image held by Filipino students. Additionally, the significance of UAl was measured when grouped according to gender identity, weekly allowance, and employment. Furthermore, the study explored the relationship between MTHS brands and passengers' preferences for features. Findings revealed that undergraduate students aged 20 to 23 years old, and female passengers, are the prevalent users of MTHS, with cash being the most commonly used payment option and commuting to school as their primary transportation purpose. Convenience in booking, safety, and sanitation ranked highest among ten service features in terms of attitude levels. Angkas emerged as the most prominent brand in terms of brand awareness. Usage frequency when grouped according to gender identity (H4; p = < 001), weekly allowance (H5; p = < 001), employment (H6; p = < .001), and levels of attitude when grouped according to gender identity (H7; p = < 001) and weekly allowance (H8; p = < .001) were found to be statistically significant. Through using multinomial logistic regression and linear regression, it was found out that promotions and discounts have a positive estimate and is statistically significant (p = 0.043), which implied that the mentioned feature may influence the respondents in choosing an MTHS app. Based on the study's outcomes, it is recommended to include a female rider option in MTHS apps. Additionally, MTHS companies should strategically create promotions to entice the passengers to book such MTHS app being the promotions and discounts was found as a decision factor. Keywords: Motorcycle Taxi, UAI Study, Usage, Attitude, Image
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2